A Multi-Objective Allocation Approach for Power Quality Monitoring Devices - Shaaban, Mostafa (2019)
With the inception of smart grids and the increased integration of renewable resources, the continuous monitoring of power systems becomes increasingly important to monitor power quality (PQ) and speed up the localization of faults. The optimal allocation of PQ monitoring devices to achieve 100% observability is one of the most important design problems that face the planning of any power system. However, for smart distribution networks (SDNs), the cost of achieving 100% observability is exorbitant. Therefore, for cost-effective monitoring, the SDN planers can sacrifice a percentage of the system observability. To that end, this paper proposes a multi-objective optimization approach for allocating the PQ monitoring devices with the aim of minimizing two conflicting objectives, namely, the cost and the loss of observability in the system. The proposed approach utilizes branch-and-reduce-based nonlinear programming global solver that minimizes both objectives. The analysis is first carried out for balanced systems and later extended to unbalanced systems. To validate the performance of the proposed approach, it is applied to different standard systems. The obtained results prove the effectiveness of the proposed approach.